1999
DOI: 10.1016/s0168-9002(98)01317-5
|View full text |Cite
|
Sign up to set email alerts
|

High rate behavior and discharge limits in micro-pattern detectors

Abstract: We present and discuss a set of systematic measurements, carried out with gaseous proportional micro-pattern detectors, in order to assess their maximum gain when irradiated with high-rate soft X-rays and heavily ionizing alpha particles. The inventory of detectors tested includes: microstrips, micromegas, micro-dot, gas electron multiplier, CAT (compteur à trous), trench (or groove), micro-CAT (or WELL) detectors, as well as systems with two elements of gaseous amplification in cascade. W e confirm the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 43 publications
4
64
0
Order By: Relevance
“…Indeed, recent observations on GEM coupling to other ampli"cation elements [20,21] suggested that the distance between the elements should not be less than 0.3}0.6 mm, or else the two ampli"cation elements are equivalent, in terms of the maximum gain, to a single one.…”
Section: Avalanche Extension Outside the Gem Holesmentioning
confidence: 99%
“…Indeed, recent observations on GEM coupling to other ampli"cation elements [20,21] suggested that the distance between the elements should not be less than 0.3}0.6 mm, or else the two ampli"cation elements are equivalent, in terms of the maximum gain, to a single one.…”
Section: Avalanche Extension Outside the Gem Holesmentioning
confidence: 99%
“…hit spatial resolution at the level of 70 µm, The first and second requirements, taking into account the moderately large area (and therefore costs), are well fulfilled by the recent GEM technology; in particular the high particle flux which corresponds to a hits rate on the tracker entrance at the level of 500 kHz/cm 2 (from simulation, the reduction is due to the low efficiency of the gamma photon detection) is well below the stable gain limit ≥ 10 MHz/cm 2 reported in literature [6]. In fact, the front tracker is based on 6 high resolution, large GEM detectors (chambers), for a total tracker length of about 50 cm.…”
Section: Gem Trackermentioning
confidence: 92%
“…All devices permit to reach gains above 10 4 . However, a systematic study of their behavior reveals the similarity of values for the maximum sustainable gain, several thousand, when exposed to alpha particles [20]. As an example, Fig.…”
Section: Transitions Part Two: Avalanche To Sparkmentioning
confidence: 96%
“…Fig. 3 illustrates the basic problem [20]. As a function of voltage, it provides the proportional gain, measured in laboratory conditions (low rate soft X-rays); the efficiency plateau for minimum ionizing particles is also shown, for a typical configuration and making use of currently available high-density electronics.…”
Section: Transitions Part Two: Avalanche To Sparkmentioning
confidence: 99%
See 1 more Smart Citation